Interior models of earthquake damaged buildings for search and rescue. Issue 1 (January 2016) - Bloch, Tanya; Sacks, Rafael; Rabinovitch, Oded
Highlights: Search and rescue (SAR) operations in buildings after an earthquake must be quick. A novel computational approach provides a building information model to aid SAR teams. Many collapse candidate models are generated before the quake from an as-built BIM. The 'best-fit' model is matched after the quake using terrestrial laser scanning. Feasibility has been demonstrated using Modal Assurance Criteria (MAC) algorithms. Abstract: Survivors trapped in void spaces formed when buildings collapse in an earthquake may be saved if search and rescue (SAR) operations are quick. A novel computational approach aims to provide building information that can guide SAR teams, thus minimizing their risk and accelerating operations. The inputs are an 'as-built' BIM model of the building before an earthquake and a partial 'as-damaged' BIM model of the exterior components after the earthquake derived from a terrestrial laser scan. A large set of possible collapse patterns is generated before the earthquake. After the event, the pattern with geometry most similar to that of the 'as-damaged' exterior BIM can be selected rapidly. This paper details the selection methods, which use least sum of point distances and Modal Assurance Criteria (MAC) algorithms, and illustrates their operation on a series of simulated computer models of collapsed structures, thus demonstrating the potential feasibility of the proposed approach.